Left Ventricular Diastolic Dysfunction In Hypertension, Diabetes Mellitus And Ischaemic Heart Disease - Shah, RK; Upadhayaya, AB; Tibrewala, L.P.; Regmi, P.R.; Acharya, K.P.; Khanal, HH; Rajbhandari, S; Nepal, B (Nepalese Heart Journal, 2004)
Congestive heart failure caused by a predominant abnormality in diastolic function is both common and causes significant morbidity and mortality. However, there is a continued controversy surroundings the definition of diastolic dysfunction and the diagnostic criteria for diastolic heart failure. Recent clinical studies have provided sufficient data to develop standardized diagnostic criteria to define diastolic heart failure.